Analisis Efektivitas Konsep Polimorfisme dalam Menyederhanakan Desain Perangkat Lunak - Atikah Nurpadhilah, Naurah; Aliya Dwi Ardiyanti; M. Aufa Rafiqi; Nur Ayu Siti Hardianti; Mufid Faruq Aziz (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Object-Oriented Programming (OOP) is a programming paradigm that emphasizes the use of objects and classes to build modular and maintainable software. One of the fundamental concepts in OOP is polymorphism, which is the ability of objects from different classes to respond to the same method in different ways. This study aims to analyze the effectiveness of the polymorphism concept in directing software design in terms of code structure, development utility, and maintenance efficiency. The research method used is a literature study and program code simulation using a procedural approach compared to an object-oriented approach that applies runtime polymorphism. The results of the analysis show that the use of polymorphism can significantly reduce the number of lines of code, logical structure traffic, and facilitate feature expansion without the need to change existing code. Thus, polymorphism has proven effective in improving readability, reusability, and scalability of software design.